The propaganda of power : the role of panegyric in late antiquity - Whitby, Mary. (Mnemosyne, Supplements, 1998)
The 13 essays presented here shed new light on the role of panegyric in the western and eastern Roman Empire in the late antique world. Introductory chapters give an overview of panegyrical theory and practice, followed by studies of major writers of the early empire and the anonymous Panegyrici latini . The core of the volume deals with prose and verse panegyric under the Christian Roman Empire (4th-7th century): key themes addressed are social and political context, the 'hidden agenda', and the impact of Christianity on the pagan tradition of the panegyric, including the portrayal of patriarchs and holy men.